Developing self-regulated learning through the use of meta-cognitive strategies in adventure-based activities - Galbraith, Ian William (Rhodes University, Faculty of Education, Department of Education, 2006)
This research investigates the benefits of adventure-based activities used as a learning experience at school level. In order to scientifically investigate these benefits the study is located at a school where an adventure-based programme is being developed as part of the school's curriculum. This programme consists of a range of adventure type experiences including, rock climbing, abseiling, canoeing, mountain biking, group dynamic activities, survival camps, ropes courses and adventure racing. At Lilyfontein School these activities form part of the Life Orientation and life Skill programmes from grade 1 to grade 11. Specialized and qualified staff are used to conduct some of these programmes. Adventure-based activities are rigorous and contain elements of risk which require problem solving, good decision making and sound emotional management. These aspects present both physical and mental challenges to any participant. This study postulates that learners engaged in these adventure type activities are faced with using meta-cognitive strategies to help them through these mental and physical challenges. In doing these activities regularly learners will develop meta-cognitive strategies that will enable them to become better self-regulated learners. A self-regulated learner is able to use meta-cognitive strategies like problem solving, decision making, selfevaluation, self-monitoring, self-reflective thinking or emotional control in life generally. The aim of this research is to conduct an on-going action research study of the adventure-based programmes to determine their worth for the learners at Lilyfontein School and consequently the future of such experiences in a school's curriculum. This forms the primary goal of this research. The secondary goal is to gather valid and reliable evidence required to make an argument for the School's Governing Body (SGB) and Curriculum Development Committee (CDC) to be able to substantiate decisions relating to any such future programmes. This research regards the school context as the activity system which forms a primary case study. In order to extract maximum information from this educational system, embedded case studies will be conducted and monitored. These embedded case studies will be made up of the following groups of people: firstly the learners engaged in a variety of adventure-based experiences, secondly the educators as they observe and perceive the consequences of these experiences, and thirdly the parents as they identifY possible influences of adventure-based experiences on the behaviours, beliefs or habits of their children. In this research study data collecting techniques are used to extract infonnation from the embedded cases. Infonnation is elicited from parents and educators through the use of questionnaires and interviews. For learners, narratives and interviews are used to get a more qualitative sense of their beliefs and feelings on adventure-based experiences. However, in order to capture and document the learners' use of metacognitive strategies as they engage in the rigours of an adventure-based activity a more empirical approach is used. This approach uses in-depth observation, recording and measuring of the learners in action. Video footage is used to record the learners' reactions as they battle with fear, mental-strength, fatigue and decision making to accomplish their goal during an adventure activity. This study claims that an adventure-based experience helps to mediate the learning that will develop selfregulatory strategies in a learner. The limited research in the adventure-based learning field and more significantly the lack of empirical evidence of how meta-cognitive strategies fonn a crucial component of adventure-based activities has meant that the researcher has developed his own recording, measuring and analytical tools to serve this end. He has chosen to use Engestrom's third generation Activity Theory model which provides a useful underlying theory as well as an analytical and interpretive framework for this study. The research was conducted over a period of three years. Findings are considered in relation to the National Curriculum Statement for the GET and FET bands to ensure its relevance in the school context to the National Department of Education's expectations for the Life Orientation curriculum. The empirical findings of this study at Lilyfontein School and their relevance to the curriculum content of the National Curriculum Statement ought to provide convincing data for very important curriculum policy decisions at Lilyfontein School and in the broader educational context.
Keywords: Lilyfontein School; Adventure education; Education -- South Africa -- Curricula; Competency-based education -- South Africa; Educational psychology; Cognitive learning